The system of liberty : themes in the history of classical liberalism - Smith, George H. 1949- (Cambridge : Cambridge University Press, 2013)
"This book demonstrates a conceptual unity within the manifestations of classical liberalism by tracing the history of several interrelated and reinforcing themes"--
Includes bibliographical references and index.
Keywords: Liberalism; Liberty; Individualism; POLITICAL SCIENCE / History & Theory